Strong m-convexity of set-valued functions - Lara, Teodoro; Merentes, Nelson; Quintero, Roy; Rosales, Edgar (Annales Mathematicae Silesianae, 2023)
In this research we introduce the concept of strong m-convexity for set-valued functions defined on m-convex subsets of real linear normed spaces, a variety of properties and examples of these functions are shown, an inclusion of Jensen type is also exhibited.